MUDAS DE KIRI (Paulownia spp.) OBTIDAS EM RELAÇÃO À DENSIDADE DE SEMEADURA - Veiga, Ricardo A. Arruda (REVISTA DE AGRICULTURA, 2016)
MUDAS DE KIRI (Paulownia spp.) OBTIDAS EM RELAÇÃO À DENSIDADE DE SEMEADURA